2011
DOI: 10.1002/cncr.26644
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of positron emission tomography/computed tomography and clinical assessment in the detection of complete rectal tumor regression after neoadjuvant chemoradiation

Abstract: BACKGROUND: Neoadjuvant chemoradiation (CRT) therapy may result in significant tumor regression in patients with rectal cancer. Patients who develop complete tumor regression have been managed by treatment strategies that are alternatives to standard total mesorectal excision. Therefore, assessment of tumor response with positron emission tomography/computed tomography (PET/CT) after neoadjuvant treatment may offer relevant information for the selection of patients to receive alternative treatment strategies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(74 citation statements)
references
References 31 publications
(61 reference statements)
1
69
0
4
Order By: Relevance
“…These impressive results have since been corroborated by a case series from Maas et al 12 as well as a number of follow-up publications by the Brazilian group. 11,[22][23][24] The proportion of patients manageable by CRT alone varies between reports, as does the incidence of local recurrence for patients followed without surgery. This is at least to some extent likely due to differences in criteria for clinical complete response: The Mass et al series of 21 patients represented merely 11% of all rectal cancers treated with CRT in the study period, but only one of those 21 patients presented with an endoluminal recurrence during a median 15 months of follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These impressive results have since been corroborated by a case series from Maas et al 12 as well as a number of follow-up publications by the Brazilian group. 11,[22][23][24] The proportion of patients manageable by CRT alone varies between reports, as does the incidence of local recurrence for patients followed without surgery. This is at least to some extent likely due to differences in criteria for clinical complete response: The Mass et al series of 21 patients represented merely 11% of all rectal cancers treated with CRT in the study period, but only one of those 21 patients presented with an endoluminal recurrence during a median 15 months of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…It should be recognised, though, that comparisons between series are complicated by disparities in the use of supplementary chemotherapy, e.g. after CRT but prior to response evaluation 23 or after allocation to observation. 12 Overall, the results of the current study are comparable to the Brazilian reports, in terms of proportion of patients classified as complete responders as well as in incidence of local recurrence in the observation group.…”
Section: Discussionmentioning
confidence: 99%
“…It should be stressed that none of the imaging investigations such as CT, MRI or PET are enough accurate that they can be used to determine whether pCR was also achieved in cCR patients [32][33][34]. In the latter, pelvic MRI is rather an auxiliary aid, since diagnosing residual lesions does not exclude the diagnosis of complete regression [31].…”
Section: Definition Of Ccrmentioning
confidence: 99%
“…Various PET-CT parameters have been investigated: mean standardized uptake value (SUVmean), maximum SUV (SUVmax), ΔSUVmax (SUVmax-pre -SUVmaxpost), response index [RI, (SUV pre -SUV post )/SUV pre ), metabolic tumor volume (MTV), ΔMTV% (MTV pre -MTV post )/MTV pre , visual response assessment (VRA), and total lesion glycolysis (TLG, SUVmean × MTV) ( Table 2) (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). These studies were able to establish a correlation between PET-CT results and CRT response (22)(23)(24)(25)(26)(27)(28)(29)(30). Most studies used several parameters but found just one or two parameters correlated with CRT response (21)(22)(23)(24)(25)(26)(27).…”
Section: Positron Emission Tomography-computed Tomography (Pet-ct)mentioning
confidence: 99%
“…Second, PET-CT scans were not successful in determining nodal status (24). Third, PET-CT has difficulty in distinguishing between residual cancer and intraluminal or physiologic mucosal activity uptake (30). Fourth, the specificity of predictive value is too low to justify modification of the standard treatment protocol for an individual patient.…”
Section: Positron Emission Tomography-computed Tomography (Pet-ct)mentioning
confidence: 99%